Abdullah cevdet's points of wives of education and some educational problems in the içtihad journal - Gündüz, Mustafa (T.C. Milli Egitim Bakanligi, 2007)
Journal of İctihad had a very special place in Turkish culture. In arguments that published in the journal, authors advocated Western philosophy. Authors wrote articles about every detail in social, political, economical, and cultural life of the age. Most of the topics that published in the journal came into life after foundation of new republic in Turkey. That means mental preparation for revolutions of new republic was done in that time. In the journal, a big number of social problems investigated in depth. One of the most important problems of that age was education. A. Cevdet touched the problem several times among the writers of the journal perhaps. General ideas of the writers of the journal are: a) education is one of the most influentical item in social change, b) education in that age was not open for revolution, c) new revolutions must be employed in all educational areas.
Abdullah cevdet'i?n e?i?ti?m görüşleri ve i?çtihad dergisinde bazı e?i?ti?m sorunlari
Keywords: Education; II. Constitution; İçtihad; Reform in education; Social change